Stochastic modeling and performance analysis in balancing load and traffic for vehicular ad hoc networks: A review - Ravi, Banoth; Kumar, Manoj; Hu, Yu‐Chen; Hassan, Shamsul; Kumar, Bittu (International journal of network management, 2023)
The rapid growth of vehicular applications has resulted in high demand for Internet technology, which demands an unprecedented network capacity and a high quality of service (QoS). In vehicular ad hoc networks (VANETs), since nodes (vehicles) are highly mobile. The dynamic nature of the network topology in the VANET system changes due to frequent changes in link connectivity. The vehicles‐to‐vehicles (V2V), vehicles‐to‐infrastructure (V2I), and QoS, as well as the heterogeneity of applications within the VANET. VANETs have been introduced to make driving comfortable by providing safety and support to drivers. Due to the flexibility and offloading schemes available in‐vehicle applications, there are some limitations. However, there are many issues in providing optimum service provisioning and scheduling in the vehicular environment. In VANETs, BSs and roadside units (RSUs) improve QoS. However, Internet services transmit packets to vehicles using stochastic models, and it predicts the traffic on a VANET. We provide open challenges to drive stochastic models in this direction.